Antioxidant and Nutritional Properties of Domestic and Commercial Coconut Milk Preparations - Asiri N. Karunasiri; Mahendra Gunawardane; Chathuri M. Senanayake; Nimanthi Jayathilaka; Kapila N. Seneviratne (International Journal of Food Science)
The aqueous extract of scraped coconut kernel is known as coconut milk. Coconut milk preparations are also commercially available in the form of desiccated powders or liquids. While these various coconut milk preparations are heavily used in cooking in the Asian countries as a major source of dietary fat, limited studies have been conducted on their chemical and nutritional composition. In this study, we have determined the chemical composition and nutritional effects of both domestic preparations of coconut milk and the commercially available counterparts. The results indicate that the phenolic compounds of all coconut milk preparations provide protection against oxidative damage on lipids and inhibit oxidative damage of both proteins and DNA. The lipid profiles are not significantly affected by the consumption of the three coconut milk preparations despite their different fat contents.